2018
DOI: 10.1093/cid/ciy311
|View full text |Cite
|
Sign up to set email alerts
|

Burden, Etiology, and Risk Factors of Respiratory Virus Infections Among Symptomatic Preterm Infants in the Tropics: A Retrospective Single-Center Cohort Study

Abstract: The burden of RVIs is high in preterm infants in the tropics, affecting >1 of 10 infants born at ≤32 weeks' gestation before 2 years of age. Respiratory syncytial virus was the main causative pathogen identified. Risk factors for RVI included extremely low gestational age, receipt of postnatal steroids, and bronchopulmonary dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Prior studies on the prevalence of respiratory pathogens have mainly focused on high risk groups such as infants and hospitalized patients or special populations, such as military recruits ( Jiang et al., 2017 ; Lau et al., 2018 ; Tan et al., 2014 ; Yeo et al., 2018 ). This study provides insights into the circulation of respiratory pathogens in febrile adults who sought medical attention at one out of five primary healthcare clinics in Singapore from December 2007 to February 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on the prevalence of respiratory pathogens have mainly focused on high risk groups such as infants and hospitalized patients or special populations, such as military recruits ( Jiang et al., 2017 ; Lau et al., 2018 ; Tan et al., 2014 ; Yeo et al., 2018 ). This study provides insights into the circulation of respiratory pathogens in febrile adults who sought medical attention at one out of five primary healthcare clinics in Singapore from December 2007 to February 2013.…”
Section: Discussionmentioning
confidence: 99%
“…A national study from Taiwan reported that a history of BPD was associated with a 1.8-14.4-fold increased risk of hospitalization for respiratory syncytial virus (RSV) compared to gestation and age-matched controls [80]. Acute care use for respiratory viral infections is also more likely to occur in younger infants [80,96]. In addition to short-term outcomes, significant respiratory infections may have long-term consequences as well, although long-term data are limited for preterm infants with respiratory disease.…”
Section: Infectionmentioning
confidence: 99%
“…Respiratory viruses such as influenza, respiratory syncytial virus (RSV), human metapneumovirus, parainfluenza, human rhinoviruses (HRV), human seasonal coronaviruses, and SARS-CoV-2 can lead to serious respiratory disease and mortality (19)(20)(21). Respiratory viral illness severity ranges from asymptomatic carriage, mild upper respiratory tract symptoms (common cold) to severe pneumonia, bronchiolitis and acute exacerbations of asthma or COPD which can be life-threatening (22).…”
Section: The Link Between Respiratory Viruses and Ifnsmentioning
confidence: 99%